The behavioral economics of John Maynard Keynes - Ronald Schettkat (University of Wuppertal, Schumpeter School of Business and Economics, 2018)
After the publication of Keynes' "General Theory," economics was frequently described as schizophrenia: (neo-) classical at the micro-level, but Keynesian at the macro-level. In actuality, Keynes' revolution was, to a substantial part, based on the behavioral micro-foundations of the world we live in, which has been dismissed as ad hocery, or simply ignored or reclassified in the neoclassical synthesis. Keynes' General Theory is truly general. It includes the full-employment equilibrium as a special case. In addition, its microeconomic foundations are broader than the extremely narrow behavioral assumption of the neoclassical model. Consequently, we argue that Keynes' microeconomics - although not fully worked out - is actually revolutionary. This may be difficult for (neo-) classical economists to accept, but it is strongly confirmed by the recent results in behavioral economics. Keynes' macroeconomics is the result of his microeconomics. Keynes' theory is a criticism of (neo-) classical economics, where he offers alternatives from micro to macro. It is truly a general theory, micro and macro.
urn:nbn:de:hbz:468-20180920-120604-6
Keywords: A1; A13; B21; B22; B31; D01; D81; D84; D9; E12; E14; E7; 330; Keynes' economics; behavioral economics; microeconomics; macroeconomics; knowledge; information; uncertainty; animal spirits